2011
DOI: 10.5194/acp-11-2933-2011
|View full text |Cite
|
Sign up to set email alerts
|

Determining the spatial and seasonal variability in OM/OC ratios across the US using multiple regression

Abstract: Data from the Interagency Monitoring of Protected Visual Environments (IMPROVE) network are used to estimate organic mass to organic carbon (OM/OC) ratios across the United States by extending previously published multiple regression techniques. Our new methodology addresses common pitfalls of multiple regression including measurement uncertainty, colinearity of covariates, dataset selection, and model selection. As expected, summertime OM/OC ratios are larger than wintertime values across the US with all regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 44 publications
11
77
0
Order By: Relevance
“…However, the magnitude of OM seasonality is similar between the observations and model with very little variation in OM throughout the year (a 35 % increase in summer over winter), in agreement with values reported by Zhang et al (2012a). The seasonality in OM (and consequently PM 2.5 ) might be enhanced if we used a varying OM/OC ratio, as studies have shown that the ratio is greater in the summer than in the winter (e.g., Simon et al, 2011). However, the ratio would be applied to both the model simulation and observations, and, as GEOS-Chem is already able to simulate the OM seasonality, would therefore not explain the model discrepancy.…”
Section: Seasonality In Aod and Surface Concentrationssupporting
confidence: 75%
“…However, the magnitude of OM seasonality is similar between the observations and model with very little variation in OM throughout the year (a 35 % increase in summer over winter), in agreement with values reported by Zhang et al (2012a). The seasonality in OM (and consequently PM 2.5 ) might be enhanced if we used a varying OM/OC ratio, as studies have shown that the ratio is greater in the summer than in the winter (e.g., Simon et al, 2011). However, the ratio would be applied to both the model simulation and observations, and, as GEOS-Chem is already able to simulate the OM seasonality, would therefore not explain the model discrepancy.…”
Section: Seasonality In Aod and Surface Concentrationssupporting
confidence: 75%
“…In these situations the nitrate measured in the fine mode is actually the tail of coarse mode nitrate. POM was computed assuming an average molecular weight per carbon weight for OC of 1.8 based on the work of Malm and Hand [2007], although it is also spatially and temporally variable, and typical values could range from 1.2 to 2.6 [ Turpin and Lim , 2001; El‐Zanan et al , 2005; Malm and Hand , 2007; Malm et al , 2011; Simon et al , 2011]. Although the POM multiplier is most likely lower in urban regions [ Turpin and Lim , 2001; Malm et al , 2011], we applied the same value to data from both networks.…”
Section: Methodsmentioning
confidence: 99%
“…For the oxidation products of the directly emitted species (LVOO1, LVOO2, SVOO1, SVOO2, SVOO3), we have chosen higher OM : OC (and thus lower carbon number) values than Koo et al (2014) to bound the typical observed range of OM : OC reported from ambient studies, including Aiken et al (2008) and Canagaratna et al (2015) for multiple US and global sites (1.3-2.25) and Simon et al (2011) for routine-monitoring networks in the continental US (0.79-2.15). The molecular weights of these species are calculated using the given carbon number and OM : OC, while assuming each representative species comprises only carbon, oxygen, and hydrogen atoms.…”
Section: Poa Semivolatile Partitioning and Agingmentioning
confidence: 99%